Influence of Enhanced Perceptual Features on Development of Neural Specialization for Arabic Print in Early Readers - Roa’a Alsulaiman; Tracy M. Centanni (Gulf Education and Social Policy Review)
Abstract Reading in Arabic is challenging for many early learners. To improve Arabic reading fluency, a new textbook (IQRA) was designed to enhance the visual characteristics of Arabic and, thus, help children recognize the Arabic orthography. Despite promising behavioral improvement, it is unknown whether this improvement is associated with accelerated development of the brain's reading network, which develops over many years. Thus, the goal of this study was to measure brain responses to Arabic print in early readers enrolled in IQRA instruction. Reading was assessed and electroencephalography (EEG) responses were collected from 49 first-grade children in the UAE (N = 27 IQRA treatment, N = 22 control) while completing a single EEG task at the end of the school year. Behavioral measures of word identification revealed a slight improvement for IQRA children compared to their peers in control classrooms. EEG responses suggest improved familiarity with Arabic in IQRA children as well as increased print-specific response, though the latter finding did not survive correction for multiple comparisons. These findings suggest a modest effect of the IQRA curriculum on neural responses to print in young readers. Future work is needed to understand the long-term impact of IQRA on the reading brain.